1995
DOI: 10.1161/01.str.26.5.834
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Autoregulation by Means of Periodic Changes in Blood Pressure

Abstract: The results support our hypothesis and may lead to a technique for assessing the competence of cerebral autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
123
1
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 7 publications
20
123
1
3
Order By: Relevance
“…The BP-BFV phase shifts were similar to those observed during the Valsalva maneuver obtained from the MMPF method [17]. Such positive phase shift has been also reported using Fourier transform methods during head-up tilt, and was interpreted as a faster recovery of BFV mediated by the compensatory cerebral autoregulatory mechanisms [8,12,14,50]. Our previous studies showed that the reduction of the MMPF derived BP-BFV phase shifts was associated with impaired cerebral autoregulation in stroke and hypertensive subjects and in patients with traumatic brain injuries [17,51], indicating that MMPF results reflect dynamics of cerebral autoregulation.…”
Section: A Assessment Of Nonlinear Interactions Between Nonstatisupporting
confidence: 75%
See 1 more Smart Citation
“…The BP-BFV phase shifts were similar to those observed during the Valsalva maneuver obtained from the MMPF method [17]. Such positive phase shift has been also reported using Fourier transform methods during head-up tilt, and was interpreted as a faster recovery of BFV mediated by the compensatory cerebral autoregulatory mechanisms [8,12,14,50]. Our previous studies showed that the reduction of the MMPF derived BP-BFV phase shifts was associated with impaired cerebral autoregulation in stroke and hypertensive subjects and in patients with traumatic brain injuries [17,51], indicating that MMPF results reflect dynamics of cerebral autoregulation.…”
Section: A Assessment Of Nonlinear Interactions Between Nonstatisupporting
confidence: 75%
“…A transfer function is typically used to explore the relationship between blood pressure (BP) and blood flow velocity (BFV) by calculating gain and phase shift between the BP and BFV power spectra [2,8,[10][11][12][13][14][15][16]. In this approach, it is presumed that signals are stationary, and are composed of superimposed sinusoidal oscillations of constant amplitude and period at a pre-determined frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…The response to this input will be denominated as the pressure-pulseresponse (PPR). Figure 2B and 3A show the expected left-shift (phase lead) in the PPR [7] resulting from the high-pass characteristics of the autoregulatory response [5,14]. Results from preliminary work [13] based on simulations using Tiecks model [15] and recorded data showed that the PPR at 1.5 seconds (A1.5) and the amplitude at 7 seconds (A7) (as shown in Fig.…”
Section: Selection Of Autoregulatory Parametersmentioning
confidence: 88%
“…Most of the studies of CA focus on linear methods [5,[7][8][9][10] with the more recent inclusion of some nonlinear approaches [8,[10][11][12][13]. Although nonlinear techniques can provide improved model fits, their benefit in assessing CA is still unclear with few studies having systematically compared them to linear alternatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation